Maternal Mortality in Peru. - Ludmir, Abraham (2015)
It is disconcerting to note that these deaths occur each year, for inadequate control, prenatal, not to use family planning methods, by technical failures in care (dependent on inadequate training of serving) or by illegal abortion.